Experimental Equipment Validation for Methane (CH4) and Carbon Dioxide (CO2) Hydrates - Khan, M.S. (Institute of Physics Publishing, 2018)
Clathrate hydrates are eminent structures regard as a threat to the gas and oil industry in light of their irritating propensity to subsea pipelines. For natural gas transmission and processing, the formation of gas hydrate is one of the main flow assurance delinquent has led researchers toward conducting fresh and meticulous studies on various aspects of gas hydrates. This paper highlighted the thermodynamic analysis on pure CH4 and CO2 gas hydrates on the custom fabricated equipment (Sapphire cell hydrate reactor) for experimental validation. CO2 gas hydrate formed at lower pressure (41 bar) as compared to CH4 gas hydrate (70 bar) while comparison of thermodynamic properties between CH4 and CO2 also presented in this study. This preliminary study could provide pathways for the quest of potent hydrate inhibitors. Â© Published under licence by IOP Publishing Ltd.